(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
A study on macroinvertebrate diversity was conducted in Sungai Kisap, Langkawi, Kedah. Five stations were selected with a distance of approximately 500 metres apart with three replications of benthos and two replications of water sample. The results classified Sungai Kisap in Class I, which indicates very good water quality based on WQI recommended by the Department of Environment. A total of 2 phyla, 3 classes, 8 orders, 29 families, and 3564 individuals were successfully sampled and recorded. The presence of Hydropsychidae, Baetidae, and Chironomidae with a high abundance of the families show the potential to be used as biological indicators of a clean ecosystem. The analysis showed that the average value of Shannon Diversity Index, H’ (1.28), Pielou Evenness Index, J’ (0.45), and Margaleff Richness Index, DMG (2.80) indicates that Sungai Kisap is in moderate condition and the distribution of macroinvertebrates is uniform between stations. The correlation test showed that the WQI has a strong relationship with the diversity indices involved. BMWP, ASPT, and FBI showed that Sungai Kisap has good water quality.